The Image of the Native Ruler in the Writings of the Participants of the Circumnavigations of the 16th century - Dmitry V. Mikheev (Журнал Фронтирных Исследований, 2023)
The article deals with the analysis of the formation of the image of the native ruler in the compositions of the participants of the first circumnavigations of the 16th century.